Proteomic analysis of patient tissue reveals PSA protein in the stroma of benign prostatic hyperplasia. Issue 8 (7th April 2014) - O'Malley, Katherine J.; Eisermann, Kurtis; Pascal, Laura E.; Parwani, Anil V.; Majima, Tsuyoshi; Graham, Lara; Hrebinko, Katherine; Acquafondata, Marie; Stewart, Nicolas A.; Nelson, Joel B.; Yoshimura, Naoki; Wang, Zhou
<x xml:space="preserve">Abstract</x> BACKGROUND Benign prostatic hyperplasia (BPH) is an age‐related disease frequently associated with lower urinary tract symptoms (LUTS) that involves hyperplasia of both epithelial and stromal cells. Stromal fibrosis is a distinctive feature of BPH, but the exact mechanisms underlying this phenomenon are poorly understood. METHODS In the current study, proteomics analyses were utilized to identify proteins altered in the BPH stromal compartment from patients with symptomatic BPH. Stromal cells were isolated from histological nodules of BPH by laser capture microdissection (LCM) and subjected to liquid chromatography/mass spectrometry. RESULTS Proteins identified included several stromal‐specific proteins involved in extracellular matrix (ECM) remodeling, focal adhesion, and cellular junctions. Additionally, the proteomics array identified the presence of luminal epithelial secretory protein PSA. Immunostaining, ELISA, and in situ hybridization analyses of BPH tissues verified the presence of PSA protein but absence of PSA mRNA in the stromal compartment. E‐cadherin was down‐regulated in BPH epithelial cells compared to normal adjacent tissues, suggesting that alteration of cellular junctions could contribute to the presence of luminal epithelial secreted proteins PSA and KLK2 in the stromal compartment. CONCLUSIONS The above findings suggest that the presence of secreted proteins PSA and KLK2 from prostate luminal epithelial cells in BPH stroma is a hallmark of BPH nodules, which could in part be due to alterations in cellular junction proteins and/or increased epithelial barrier permeability. Elucidating the cause and consequence of these secreted proteins in the stromal compartment of BPH may lead to new understanding of BPH pathogenesis as well as approaches to prevent and/or treat this common disease. Prostate 74:892–900, 2014. © 2014 Wiley Periodicals, Inc.